Two Trees with Heterogeneous Beliefs: Spillover Effect of Disagreement. (August 2019) - Han, Bing; Lu, Lei; Zhou, Yi
Abstract : In a model where investors disagree about the fundamentals of two stocks, the state-price density depends on investor disagreements for both stocks, especially the larger stock. This implies that disagreement among investors in a large firm has a spillover effect on the pricing of other stocks owned by these investors. The pricing effects of investor disagreements crucially depend on the average belief biases. Empirical findings support the novel model prediction of a disagreement spillover effect and help reconcile some mixed evidence in the literature.